SOC 493 (01): SOCIOLOGY OF SPORT - Kaufman, Peter (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSE OBJECTIVES Of all the social institutions that sociologists study—family, religion, media, government, medicine, education—sport is arguably the least studied in proportion to its societal impact. All throughout our lives we feel the power of sport through our roles as fans, players, and consumers. Even those who despise sports and who never participate are (un)consciously influenced by sport. Despite this omnipresence, sport remains a topic of inquiry that is routinely ignored by sociologists and social scientists alike. This omission is especially perplexing given that many of the themes that sociologists study such as socialization, corporate power, social interaction, and the intersection of race, class, and gender, directly impact or are impacted by sport. Using the sociological imagination as our base, this course attempts to analyze the ubiquity and the impact of sport. While much of our focus will be on the United States, we will also explore the power and persuasion of sport in a global context. As a course in sociology, we will approach the topic of sport from a critical perspective focusing specially on gender, race, class, and power. We will be raising questions about the institution of sport and we will explore the intended and unintended consequences that result from our collective pursuit of sport. One of our main objectives will be to identify, and then deconstruct, the far-reaching effects of sport in our everyday lives.